1965
DOI: 10.4039/ent971002-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex Pheromone of the Oriental Fruit Moth Grapholitha molesta (Busck) (Lepidoptera: Tortricidae)

Abstract: The existence of a chemical female sex pheromone in the Oriental fruit moth has been demonstrated; it both attracts and sexually excites adult males. Males without antennae are neither attracted to, nor sexually stimulated by, the pheromone. Thus, the pheromone appears to be essential for reproduction. Active pheromone can be extracted with benzene from the tips of virgin female abdomens and bioassayed with males. The gland believed to produce the pheromone was located and examined histologically. It is now po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…This time point coincides with that in previous studies that have reported that sexual activity of G. molesta was observed 2-3 hr before sunset in field observation (Gentry et al, 1975) and a few hours before lights-off in a laboratory observation (George, 1965). This is interesting as it suggests the possible involvement of GmolGOBPs in sexual activity of G. molesta.…”
Section: Discussionsupporting
confidence: 85%
“…This time point coincides with that in previous studies that have reported that sexual activity of G. molesta was observed 2-3 hr before sunset in field observation (Gentry et al, 1975) and a few hours before lights-off in a laboratory observation (George, 1965). This is interesting as it suggests the possible involvement of GmolGOBPs in sexual activity of G. molesta.…”
Section: Discussionsupporting
confidence: 85%
“…Virgin females came from a colony obtained from P. W. Shearer (Rutgers Agricultural Research and Extension Center, Bridgeton, NJ) in spring 2000. Larvae were reared on a pinto bean-based diet (Shorey and Hale 1965) at 24ЊC and a photoperiod of 16:8 (L:D) h. Pupae were segregated by sex (George 1965), and females reared individually at room temperature under natural light conditions in 118-ml plastic cups, each containing a 2-cm-long cotton wick soaked in 5% sucrose solution to feed the emerged adults. Paraffin Disk Experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The female sex pheromone of G. molesta was identified as a mixture of (Z)-8 dodecenyl acetate (Z8À12: Ac), (E)-8 dodecenyl acetate (E8-12: Ac), and (Z)-8 do-decen-1-ol (Z8À12: OH) (George 1965;Roelofs et al 1969). Previous studies showed that the blend of the three pheromone components is more effective in eliciting male response than any single component (Baker & Card e 1979;Baker et al 1981).…”
Section: Introductionmentioning
confidence: 99%